Tarascon medical translation pocketbook - Donaldson, Ross I. (Jones and Bartlett, 2010)
"This current, quick, and concise reference translates the most common phrases used in patient interviews in 17 languages including: Arabic, Farsi, French, German, Hindi, Italian, Japanese, Korean, Mandarin, Polish, Portuguese, Russian, Spanish, Tagalog, Thai, Ukrainian, and Vietnamese. Each language chapter is organized in the order of a classic medical history and contains commonly used medical phrases translated into the native language as well as guidance to the pronunciation through a unique Universal Pronunciation Guide."